2016
DOI: 10.3892/mco.2016.732
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric modulated arc radiotherapy of the whole larynx, followed by a single affected vocal cord, for T1a glottic cancer: Dosimetric analysis of a case

Abstract: Abstract. Radiation therapy (RT) and endolaryngeal surgery are standard treatments for early-stage glottic cancer. They have closely matched oncological outcomes; however, it is debatable which method is superior in terms of functional outcomes. Several dosimetric studies have demonstrated that, compared with conventional RT, intensity-modulated RT (IMRT) reduces unnecessary radiation of the adjacent normal tissues, including the carotid artery and thyroid gland. However, RT targets the whole larynx, whereas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Recently, one study showed an interesting outcome that single vocal cord irradiation using IMRT improved voice quality compared to conventional techniques [34]. IMRT reduced the RT dose to the contralateral vocal cord in several dosimetric studies [35][36][37]. In addition, the necessity of adjuvant RT may result in poorer functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study showed an interesting outcome that single vocal cord irradiation using IMRT improved voice quality compared to conventional techniques [34]. IMRT reduced the RT dose to the contralateral vocal cord in several dosimetric studies [35][36][37]. In addition, the necessity of adjuvant RT may result in poorer functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of advanced RT technologies with minimal impact to surrounding normal tissues is worthwhile in such cases. There are many reports on IMRT for early-stage glottic cancer [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], but no reports have yet detailed the dose distribution characteristics of PT for early-stage glottic cancer. In this study, we therefore aimed to clarify the dose distribution between IMRT and PT for early-stage glottic cancer and examined the usefulness of PT for early-stage glottic cancer.…”
Section: Introductionmentioning
confidence: 99%